Quantification of Bioactives and Bioactivities in Different Parts of Abelmoschus esculentus - Astutiningsih, Christina; Suharsanti, Ririn; Ismail, Wan Ismahanisa; Sufiyanto, Mohammad Imam; Minah, Faidliyah Nilna; Firmiaty, Sri (Biosaintifika: Journal of Biology & Biology Education, 2025)
The presence of natural antioxidants in medicinal plants plays a crucial role in inhibiting the detrimental effects of oxidative stress. The aim of this research is to explore more deeply all parts of A. esculenta L from flowers, fruits, seeds, leaves, and stems for the levels of compounds and antioxidant and enzyme inhibitor activities. The flowers demonstrated the highest TPC with 173.15942 ± 6.5083 mg GAE/g. The stems exhibited the lowest TPC value at 69.1967 ± 2.8408 mg GAE/g. The flowers also showed TFC value of 83.157 ± 2.021 mg QE/g while the stems displayed the lowest with 36.7240 ± 1.337 mg QE/g. IC50 value that the flowers possessed the highest antioxidant activity with 22.6539 ± 1.6452 mg/mL, whereas the stems displayed a slightly lower. In terms of the inhibitor of a-amylase activity, the flowers had an IC50 value of 102.4885 ± 11.4370 mg/mL whereas the stems had a lower. The highest IC50 value of the a-glucosidase inhibitor was 76.95 ± 12.0888 mg/mL in the flowers, and the lowest was in the stems. The highest IC50 of pancreatic lipase inhibitor was 109.5943 ± 9.7391 mg/mL in the flowers, and the lowest was in the stems. This study show that there is a relationship between the high content of total phenolic and total flavonoids on antioxidants, antidiabetic and antilipase activities.